Conversational Analysis: A Holding the Turn on A Trans “Mother” Debates Matt Walsh on Womanhood - Fatia Novita Sari; Ambalegin Ambalegin (LPPM Universitas Putera Batam, 2023)
The aimed of this research are to examined conversation analysis, specifically turn-taking strategy by type of holding the turn in a channel, YouTube of Matt Walsh, A Trans “Mother” Debates Matt Walsh on Womanhood. This research was used a qualitative technique by Creswell and Sudaryanto and Stenstroom's framework was used to assess the turn-taking strategy used in the conversation, with types of holding the turn being filled pause, repetition, and silent pause. The analysis consists of four steps: watching A Trans “Mother” Debates Matt Walsh on Womanhood, creating the transcription of the dialogue, and the data must be classified and interpreted. According to the findings of this study, a turn-taking strategy appears in the conversation. Filled pauses or verbal fillers, repetition, and silent pauses were all present. Filled pauses of verbal fillers and repetition are the most commonly employed turn-taking strategies on the data source. Therefore, this study suggests that conversation analysis is important for understanding the intent of people's speech. Furthermore, this research can be used to reflect on both theoretical and practical contributions. This study lends credence to the hypothesis of conversation analysis in turn-taking strategy. The researchers found the data of filled pause (5), repetition (4), and silent pause (1).